2014
DOI: 10.1016/j.abb.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Initial characterization of Fom3 from Streptomyces wedmorensis: The methyltransferase in fosfomycin biosynthesis

Abstract: Fosfomycin is a broad-spectrum antibiotic that is useful against multi-drug resistant bacteria. Although its biosynthesis was first studied over 40 years ago, characterization of the penultimate methyl transfer reaction has eluded investigators. The enzyme believed to catalyze this reaction, Fom3, has been identified as a radical S-adenosyl-L-methionine (SAM) superfamily member. Radical SAM enzymes use SAM and a four-iron, four-sulfur ([4Fe-4S]) cluster to catalyze complex chemical transformations. Fom3 also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 44 publications
2
81
0
Order By: Relevance
“…The relative stoichiometry of iron and sulfide bound by the as-isolated protein was determined to be 7.4 ± 1.4 and 3.7 ± 0.8 per polypeptide, respectively, consistent with the presence of a [4Fe-4S] cluster. Apparent excess iron has been observed with other RS enzymes (11,14), and was similarly seen in an alanine variant control.…”
Section: Significancementioning
confidence: 77%
See 2 more Smart Citations
“…The relative stoichiometry of iron and sulfide bound by the as-isolated protein was determined to be 7.4 ± 1.4 and 3.7 ± 0.8 per polypeptide, respectively, consistent with the presence of a [4Fe-4S] cluster. Apparent excess iron has been observed with other RS enzymes (11,14), and was similarly seen in an alanine variant control.…”
Section: Significancementioning
confidence: 77%
“…1). Although other RS cobalamin-dependent enzymes that act on carbon have been investigated previously (9)(10)(11)(12), to our knowledge this is the first in vitro characterization of a RS methylase acting sequentially to form a side chain.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup of recently characterized radical SAM methyltransferases involved in secondary metabolite biosynthesis in bacteria contain a vitamin B 12 (cobalamin)-binding motif and require cobalamin for activity (13,(31)(32)(33)(34). These enzymes are thought to use one molecule of SAM in typical radical SAM fashion to produce Ado-CH 2 · for substrate radical formation (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In streptomycetes there are Cbl-dependent enzymes that catalyze a set of modifications to peptides or polyketides or other chemical backbones during the biosynthesis of antibiotics. For instance, the methylation of the antibiotics clorobiocin and fosfomycin is a cobalamin-dependent reaction (17,18). Looking further afield, it has been reported that Cbl interacts with a riboswitch to regulate the expression of the ribonucleotide reductase nrdABS operon in Streptomyces coelicolor A3(2) (19).…”
mentioning
confidence: 99%